Virtual breast cancer education and support group for self-care management and function: a study protocol applying Person-centered principles. - Fleischer, Anne; Callahan, Ann M.; Christopher, Karina; Cummings, Ashley; Davies, Claire C. (Physical Therapy Reviews, 2020)
Background: Breast cancer survivors (BCS) may be limited in their ability to attend support groups due to transportation, geography, finances, and/or time. Evidence suggests that internet platforms, texting, and videoconferencing can be used to provide education and support. Objective: To evaluate if participating in Virtual Breast Cancer Education and Support Group (VBCESG) sessions via Zoom® videoconferencing will change perceived satisfaction and ability for survivors to complete their chosen activities. Methods: Support group flyers were posted on social media, emailed, and/or faxed to breast cancer providers and survivors to recruit participants. Inclusion criteria included participants who were diagnosed with Stage 0-III breast cancer, completed treatment, excluding HER2 suppressant and/or anti-hormone medications, and had internet access and basic computer skills. Canadian Occupational Performance Measure (COPM) was administered via Zoom® videoconferencing before the first and after the sixth VBCESG session. Based on BCS interests and information gained from the COPM and a survey, each education session was developed to address participants' identified interests. Participants received an activity tracker to count their steps. After each session, participants completed a brief survey to provide feedback on the quality of the session. Data analysis will include descriptive and inferential statistics to assess changes in perceived performance and satisfaction of BCS important activities and step counts, and BCS satisfaction with the VBCESG. COPM and survey open-ended question responses will be analyzed thematically. Plan: Results of this pilot study will inform the design and implementation of a future study to examine the perceived functional impact of VBCESG.